2022
DOI: 10.3389/fpls.2022.829069
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic Medicago truncatula Plants That Accumulate Proline Display Enhanced Tolerance to Cadmium Stress

Abstract: Cadmium (Cd) accumulation in agricultural soils constitutes a serious problem for crop yields and food safety. It is known that proline (Pro) can rapidly accumulate in plant tissues in response to abiotic stress. To analyze the potential protective effect of Pro accumulation against Cd toxicity, we compared the response to Cd stress of wild-type (WT) Medicago truncatula and a transgenic line that we had previously obtained and characterized (p18), which expressed the Δ1-pyrroline-5-carboxylate synthetase gene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 71 publications
(107 reference statements)
0
3
0
Order By: Relevance
“…Rhizobial inoculation has been previously described to promote proline accumulation under cadmium [73] or salt stress [50]. This is in agreement with previous studies by our group that show that transgenic M. truncatula plants that accumulate proline are more tolerant to salt and Cd stress [23,74]. MsProDH expression was higher in inoculated than in fertilized plants.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Rhizobial inoculation has been previously described to promote proline accumulation under cadmium [73] or salt stress [50]. This is in agreement with previous studies by our group that show that transgenic M. truncatula plants that accumulate proline are more tolerant to salt and Cd stress [23,74]. MsProDH expression was higher in inoculated than in fertilized plants.…”
Section: Discussionsupporting
confidence: 92%
“…The primary defense against ROS includes superoxide dismutase (SOD) enzymes that catalyze the dismutation of O 2 − (superoxide) to O 2 and H 2 O 2. Then, catalases and peroxidases detoxify H 2 O 2 [23].…”
Section: Introductionmentioning
confidence: 99%
“…These results are consistent with those reported by Gao et al (2009) who showed that salt stress can significantly increase the Pro content in plants. Thus, stress can promote the natural responses of plant tissues to induce the transformation and accumulation of a large amount of Pro ( García de la Torre et al., 2022 ), thereby improving the osmoregulatory and stress alleviation abilities of plant tissues under adverse conditions and assisting in the maintenance of normal plant metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Transgenic Medicago truncatula expressing Delta(1)-pyrroline-5-carboxylate synthetase (P5CS) has been established by Verdoy et al (2006) by infecting the host plant with Agrobacterium rhizogenes EHA105 carrying VaP5CS from Vigna aconitifolia. The VaP5CS gene in transgenic Medicago truncatula has been reported as being involved in conferring cadmium tolerance by enhanced proline accumulation and antioxidant activity by Garcıá de la Torre et al, (2022). Very limited attempts at genetic engineering in medicinal plants have been reported till date.…”
Section: Genetic Engineering Approachesmentioning
confidence: 99%
“…In Catharanthus roseus , the expression of terpenoid indole alkaloid (TIA) genes like STR, DAT, SGD, SLS, PRS, TDC, MTs, TPT, and MDR has been triggered under Cd toxicity ( Chen et al., 2018c ). In the comparative study of Cd-sensitive and Cd-tolerant Medicago truncatula , it was found that the overexpression of GSH and phytochelatin biosynthesis genes such as MtCYS, MtγECS, MtGSHS, MtGR, and MtG6PDH in Cd sensitive plant ( García de la Torre et al., 2022 ). While the enhanced expression of metallothionein genes from the families MT1, MT2 and MT3 in response to Cd stress in Phytolacca americana was reported by Chen et al.…”
Section: Effect Of CD At the Molecular Levelmentioning
confidence: 99%